A humanized anti‐cocaine mAb antagonizes the cardiovascular effects of cocaine in rats - Sheryl E. Koch; Jordan A. Marckel; Jack Rubinstein; Andrew B. Norman (Pharmacology Research & Perspectives, 2023)
Abstract The recombinant monoclonal anti‐cocaine antibody, h2E2, sequesters cocaine in plasma increasing concentrations more than 10‐fold. The increased levels of cocaine in the plasma could have detrimental peripheral effects, particularly on the cardiovascular system. We investigated the duration and magnitude of the effect of cocaine on the rat heart, and if h2E2 could antagonize that effect. Echocardiography was used to evaluate cardiac function under isoflurane anesthesia, while a tail‐cuff was used to measure blood pressure. Cocaine was delivered intravenously and the rats were continuously monitored for a total of 45 min. Echocardiography measurements were recorded every 5 min and blood pressure measurements were recorded throughout the duration of the experiment using 30‐s cycles. ECG recordings were taken simultaneously with the echocardiography measurements. An increase in ejection fraction was seen after the cocaine push with the maximum change occurring at 25 min. Treatment with h2E2 1 h before the cocaine push did not have any effect on cardiac parameters. Subsequent cocaine treatment had no effect on the ejection fraction, indicating that the antibody‐bound cocaine does not affect the heart. This antagonism of cocaine's effects was greatly decreased after 1 week and entirely absent after 1 month. Cocaine in the presence of h2E2 is pharmacologically inert and h2E2 may have additional clinical utility for reversing cocaine effects on the cardiovascular system.